Influência do efeito de borda, da perda de habitat e de fatores abióticos na estrutura da comunidade lenhosa em fragmentos de cerrado denso na Alta Bacia do rio Araguaia - Siqueira, Mariana Nascimento (2016)
Anthropogenic changes have changed land cover patterns and caused fragmentation of ecosystems. These changes have several consequences for biodiversity, such as habitat loss and isolation, creation of anthropic matrix, and edge effect. Few studies have evaluated the effects of fragmentation in the Cerrado, especially the effects on vegetation structure and abiotic attributes of savanna formations. Here, we sampled 17 fragments of Dense Cerrado in the Upper Rio Araguaia basin, which is a highly fragmented area. Specifically, we compared the more altered Sub-basin of the Rio Claro with the more conserved Sub-basin Rio Garças. Fragments had the fragile Quartzipsamment soils. All fragments were larger than 50 ha and had pasture matrix. Specifically, we asked the following questions: 1) What is the percentage of area lost by fragments in the last 30 years? 2) How area loss influence the woody plant community structure? 3) The species composition similarity decreases with geographical distance between fragments? 4) The edge-interior gradient affects the woody plant community structure? 5) How microclimate and physico-chemical variables vary along an edgeinterior gradient? 6) The community structure of woody plants is influenced by microclimate and physico-chemical characteristics of the soil? We sampled all woody plants with diameter ground higher than 30 cm or equal to 5 cm, in three 20 x 50 m plots along a edge-interior gradient in each fragment. We collected soils between 0 to 20 cm deep in all plots and the matrix. The air and soil temperatures, air humidity, altitude, geographical position, and light intensity were collected along with soil samples. We recorded 8,749 woody plants, belonging to 131 species. Fragment area was significantly reduced between 1985 and 2013, but the historical and current area were not associated with community structure and species diversity. We also did not find a correlation between compositional similarity and geographic distance between fragments. Additionally, 2,877 individuals of 116 species occurred at the edge, 3,038 individuals of 110 species occurred at intermediate environments, and 2,995 individuals of 107 species occurred in the center of fragments. However, species composition and community structure did not differ along the edge-interior gradient. Also, abiotic variables did not differ along the matrix-edge-interior gradient. However, these variables differed between the two sub-basins. The Rio Claro Sub-basin had higher values of Ca/CTC and xiii Ca/K, which are related to nutrient availability in the soil. The spatial distribution of plant species was influenced by altitude, humidity, silt, organic matter, pH, and calcium.